2008
DOI: 10.2138/am.2008.2932
|View full text |Cite
|
Sign up to set email alerts
|

Leucite at high pressure: Elastic behavior, phase stability, and petrological implications

Abstract: Elastic and structural behavior of a natural tetragonal leucite from the volcanic Lazium district (Italy) were investigated at high pressure by in situ single-crystal X-ray diffraction with a diamond anvil cell under hydrostatic conditions. A first-order phase transition, never reported in the literature, was observed at P = 2.4 ± 0.2 GPa from tetragonal (I4 1 /a) to triclinic symmetry (analysis of diffraction intensities suggests the space group P1), accompanied by a drastic increase in density of about 4.7%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 35 publications
6
35
0
1
Order By: Relevance
“…Moreover, since a structure refinement of the primitive high-pressure polymorph cannot be carried out, a univocal space group assignment is not possible. However, we expect that the P-induced phase transition is displacive in character, as already observed for other openframework compounds at high pressure (e.g., [27][28][29][30]). If a centric structure model is assumed for the low-pressure polymorph (with sp.…”
Section: P-induced Phase Transitionsupporting
confidence: 59%
“…Moreover, since a structure refinement of the primitive high-pressure polymorph cannot be carried out, a univocal space group assignment is not possible. However, we expect that the P-induced phase transition is displacive in character, as already observed for other openframework compounds at high pressure (e.g., [27][28][29][30]). If a centric structure model is assumed for the low-pressure polymorph (with sp.…”
Section: P-induced Phase Transitionsupporting
confidence: 59%
“…The relaxation mechanisms lead to a strong distortion of the four-and six-membered rings, along with a rearrangement of the extra-framework species. Gatta et al (2008aGatta et al ( , 2009a investigated the highpressure behaviour of leucite and pollucite, respectively and Ori et al (2008b) described that of wairakite. These experiments showed that P-induced high-symmetry to low-symmetry phase transitions occur in zeolites of ANA-framework type: leucite has a first-order phase transition from tetragonal to triclinic symmetry (I4 1 /a ?…”
Section: Hp-behaviour Of Zeolitesmentioning
confidence: 99%
“…These are compositional end members distinguished by the interstitial ions typically found in the structural channels. Analcime is the Na end member (ideally Na 16 ) also has ANA framework topology, but is not a zeolitic aluminosilicate framework and we do not consider it further. The aluminosilicate end members have broadly similar behaviour under pressure, transforming displacively at relatively low pressures (< 1-3 GPa) from a high-symmetry ambient form to a very low-symmetry compressed form.…”
Section: Copyright C Epla 2011mentioning
confidence: 99%